GOOD CORPORATE GOVERNANCE AND IDIOSYNCRATIC RISK - Metta Dewi; Yoga Rima Hadi; Sung Suk Kim (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Capital Asset Pricing Model (CAPM) is an asset pricing model that is often used by investors. In CAPM risk comes from two factors, systematic risk and unsystematic risk (idiosyncratic risk). In recent decades the risk of idiosyncratic continues to increase. Although idiosyncratic risk can be eliminated by diversification, several studies have shown that this risk cannot be completely eliminated. This study aims to analyze the effect of institutional ownership, independent board of commissioners, timeliness of financial statements on idiosyncratic risk. The sample of this research is companies engaged in the financial sector consisting of banking companies, insurance companies, securities companies, financing institutions, and others on the IDX in 2013-2018. The result of the analysis shows that the independent board of commissioners has a significant negative effect on idiosyncratic risk. Institutional ownership has a positive effect and timeliness of financial statements has a negative effect, but both are not statistically significant.